PERAN GANDA STAF TU DALAM MENJAGA KUALITAS LAYANAN ADMINISTRASI DI MTS. AL-WASHLIYAH KM. 6 - Hasyim Basid; Muhammad Rifa’i (Jurnal Manajemen Pendidikan, 2026)
This study aims to understand the phenomenon of dual role among administrative staff in maintaining administrative service quality at MTs. Al-Washliyah Km. 6 Medan. The background of this study is based on the challenges faced by Islamic educational institutions in developing administrative service quality in line with technological advancement and community demands for responsive and accountable services. Administrative staff are positioned as the frontline that interacts directly with daily administrative work dynamics, however they often выполняют not only administrative tasks but also additional tasks as educators. This study uses a qualitative approach with descriptive design. Data collection was conducted through in-depth interviews, observation, and documentation. Research informants consisted of the principal, administrative staff, and students as service users. The findings show that administrative staff at MTs. Al-Washliyah Km. 6 hold dual roles as administrative officers and educators simultaneously. This condition affects administrative service quality in terms of service speed, work focus, and administrative accuracy. Time allocation is conducted flexibly and situationally, by prioritizing learning activities due to fixed schedules. Nevertheless, administrative service quality can still be maintained through professionalism, responsibility, cooperation among employees, utilization of digital technology, as well as support from the principal and adequate facilities. In the perspective of Islamic Education Management, the dual role of administrative staff reflects the values of trust (amanah), responsibility, and dedication to Islamic educational institutions.